Analysis of The Effect of Training on Houseman's Job Performance In Taman Anggrek Condominium - Kusumaningrum, Anisa Putri; Pradini, Gagih; Agustiani, Fitri (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
At this time, some people in Jakarta can be classified as very busy and need conveniences in their lives. Likewise, residences with modern facilities, are located in strategic locations. To respond to this, PT Mulia Inti Pelangi built the Taman Anggrek Condominium which is equipped with complete facilities and comfort for its residents in a strategic location. In order for the facilities for residents to be well maintained, it requires good maintenance and arrangement. Therefore, Taman Anggrek Condominium requires a Housekeeping Department. In charge of maintaining, maintaining and maintaining the cleanliness of existing facilities. This department has several sections, one of which is a houseman section whose job is to protect the public area of the entire Taman Anggrek Condominium. And to keep the houseman's work performance from decreasing training is needed. This research was made in order to determine the effect of training on the job performance of the houseman. The Research method used is the correlation coefficient, which is used to find the strength of the relationship between two variables and to further strengthen the hypothesis used.